A graph game model for software tamper protection - Dedic, Nenad; Jakubowski, Mariusz; Venkatesan, Ramarathnam (Information Hiding 2007, 2007)
We present a probabilistic program-transformation algorithm to render a given program tamper-resistant. In addition, we suggest a model to estimate the required effort for an attack. We make some engineering assumptions about local indistinguishability on the transformed program and model an attacker’s steps as making a walk on the program flow graph. The goal of the attacker is to learn what has been inserted by the transformation, in which case he wins. Our heuristic estimate counts the number of steps of his walk on the graph. Our model is somewhat simplified, but we believe both the constructions and models can be made more realistic in the future.